Origins and Spatial Distribution of Non-Pure Sulfate Particles (NSPs) in the Stratosphere Detected by the Balloon-Borne Light Optical Aerosols Counter (LOAC) - Jean-Baptiste Renard; Gwenaël Berthet; Anny-Chantal Levasseur-Regourd; Sergey Beresnev; Alain Miffre; Patrick Rairoux; Damien Vignelles; Fabrice Jégou (Atmosphere, 2020)
While water and sulfuric acid droplets are the main component of stratospheric aerosols, measurements performed for about 30 years have shown that non-sulfate particles (NSPs) are also present. Such particles, released from the Earth mainly through volcanic eruptions, pollution or biomass burning, or coming from space, present a wide variety of compositions, sizes, and shapes. To better understand the origin of NSPs, we have performed measurements with the Light Optical Aerosol Counter (LOAC) during 151 flights under weather balloons in the 2013–2019 period reaching altitudes up to 35 km. Coupled with previous counting measurements conducted over the 2004–2011 period, the LOAC measurements indicate the presence of stratospheric layers of enhanced concentrations associated with NSPs, with a bimodal vertical repartition ranging between 17 and 30 km altitude. Such enhancements are not correlated with permanent meteor shower events. They may be linked to dynamical and photophoretic effects lifting and sustaining particles coming from the Earth. Besides, large particles, up to several tens of μm, were detected and present decreasing concentrations with increasing altitudes. All these particles can originate from Earth but also from meteoroid disintegrations and from the interplanetary dust cloud and comets.